Analysis of Legal Protection for the Protected and Well-Known Eiger Fashion Brand in Facing the Global Market - Sulasno Sulasno; Cindi Nur Febriani; Inge Dwisvimiar (JURNAL AKTA, 2026)
Legal protection of intellectual property, particularly trademarks, plays a significant role in enhancing business competitiveness in the era of globalization. This study aims to analyze the trademark protection of the Eiger brand in its efforts to penetrate the global market and to examine legal remedies against passing off under Law Number 20 of 2016 concerning Trademarks and Geographical Indications. This research employs a qualitative method with an empirical juridical approach. The data used consist of primary, secondary, and tertiary sources, which are analyzed descriptively. The findings indicate that trademark owners possess exclusive rights to use and protect their trademarks from unauthorized use. In the international context, trademark protection is territorial in nature; therefore, Eiger must register its trademark in target countries or through international mechanisms such as the Madrid Protocol. Strong trademark protection helps maintain brand reputation, prevent counterfeiting, and increase consumer confidence in global markets. However, differences in legal systems across countries and the widespread circulation of counterfeit products remain significant challenges. Trademark protection serves as a strategic instrument for strengthening Eiger’s competitiveness in the international market. In cases of trademark infringement or passing off, legal remedies under Law Number 20 of 2016 include civil lawsuits before the Commercial Court to stop infringement and seek damages, criminal prosecution of offenders, and administrative measures such as the cancellation or removal of trademarks registered in bad faith.